Agriculture diversification in South Asia: patterns, determinants, and policy implications - Joshi, Pramod Kumar; Gulati, Ashok; Birthal, Pratap Singh; Tewari, Laxmi (International Food Policy Research Institute, 2003)
The South Asian countries are gradually diversifying with some inter-country variation in favor of high value commodities, namely fruits, vegetables, livestock and fisheries. Agricultural diversification is strongly influenced by price policy, infrastructure development (especially markets and roads), urbanization and technological improvements. Rainfed areas have benefited more as a result of agricultural diversification in favor of high value crops by substituting inferior coarse cereals. Agricultural diversification is also contributing to employment opportunities in agriculture and increasing exports. The need is to suitably integrate production and marketing of high value commodities through appropriate institutions. Market reforms in developing and strengthening desired institutions through required legal changes would go a long way in boosting agricultural growth, augmenting income of small farm holders and promoting exports.